2010
DOI: 10.1007/s00128-010-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polychlorinated Biphenyls and Mercury Levels in Soil and Biological Samples from San Felipe, Nuevo Mercurio, Zacatecas, Mexico

Abstract: The aim of this work was to evaluate contamination by polychlorinated biphenyls and mercury in soil, and to assess exposure level to both contaminants in children living in San Felipe, Nuevo Mercurio, Zacatecas, Mexico. We found soil levels of total polychlorinated biphenyls ranging from non detectable (nd) to 190 μg/kg. Mercury soil levels ranged from 8.9 to 10215.0 mg/kg. Exposure levels of total polychlorinated biphenyls assessed in blood and urinary mercury in children living in the studied community were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 6 publications
0
8
3
1
Order By: Relevance
“…The mean level for total PCBs in blood was 5,892.1 ng/g lipid and the levels ranged from 2,584.9 to 14,547.9 ng/g lipid. The levels in this study are higher than levels found in different studies in Mexico (Trejo-Acevedo et al 2009;Costilla-Salazar et al 2011). For example, in a study performed in 2009, the total PCBs levels found in a community in Queretaro, Mexico was 1,253 ng/g lipid (Trejo-Acevedo et al 2009).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…The mean level for total PCBs in blood was 5,892.1 ng/g lipid and the levels ranged from 2,584.9 to 14,547.9 ng/g lipid. The levels in this study are higher than levels found in different studies in Mexico (Trejo-Acevedo et al 2009;Costilla-Salazar et al 2011). For example, in a study performed in 2009, the total PCBs levels found in a community in Queretaro, Mexico was 1,253 ng/g lipid (Trejo-Acevedo et al 2009).…”
Section: Resultscontrasting
confidence: 46%
“…For example, in a study performed in 2009, the total PCBs levels found in a community in Queretaro, Mexico was 1,253 ng/g lipid (Trejo-Acevedo et al 2009). In other hand, in San Felipe Nuevo Mercurio, Zacatecas, Mexico, the mean levels found in children living in that community was 1,600 ng/g lipid (Costilla-Salazar et al 2011). When compared PCBs levels in blood found in this study with levels reported in others studies around the world, we can note that children living in El Ramonal had higher levels (5,892.1 ng/g lipid) than children living in China (40.6 ng/g lipid; Shen et al 2010) and children living in the Slovak Republic (352.8 ng/g lipid; Trnovec et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…[10] When the PCBs levels found in our study were compared with the PCBs levels found in other locations worldwide, the levels in the present study were generally higher than those found in other studies, including urban, rural, industrial, agricultural, e-waste areas and municipal dump sites soils. [7,[11][12][13] For example, in a study performed by Ilyas et al, [13] who assessed PCBs contamination in surface soils from Surabaya, Indonesia, at various locations, such as industrial, urban, rural, dumping sites and agricultural areas, decreasing levels of these contaminants were observed, which followed the order: industrial district (9.6 mg kg ¡1 ), urban (4.7 mg kg ¡1 ), dumping site (4.1 mg kg ¡1 ), rural (2.8 mg kg ¡1 ) and agricultural areas (0.085 mg kg ¡1 ). Moreover, the PCBs Table 4.…”
Section: Discussionmentioning
confidence: 97%
“…The PCBs analyses were performed as described by Costilla-Salazar et al [7] Briefly 1 g of soil was accurately weighed and placed in Green-Chem LEV glasses, and 14 mL of dichloromethane were added. The extraction was performed in a microwave oven (CEM), and the sample was allowed to cool to 4 C in a cold-room.…”
Section: Analyses Of Pcbs In Soilmentioning
confidence: 99%
“…Moreover, it was noted that populations are exposed to proinflammatory compounds (as DDE and PCB153) and compounds such as PAHs, PCBs, and TCCD (AhR agonists) simultaneously (Costilla-Salazar et al, 2011;Martínez-Salinas et al, 2011;PerezMaldonado et al, 2013;Trejo-Acevedo et al, 2012). Thus, it is important to assess potential toxicological interactions between components of a chemical mixture in exposed populations.…”
Section: Discussionmentioning
confidence: 99%